Powertrain test bench system - Fonte, Pedro M (2019)
In parallel with major automotive manufacturers, some smaller companies are trying to launch their own electric or hybrid-propulsion models. During the development of these prototypes some tests must be done, namely consumption, autonomy, batteries state-of-charge, gradability, among others. The results of these tests can lead changes in design, motorization or battery packages. This paper presents a powertrain test bench system in order to test electrical vehicles. Regarding the automobile sector, and due to EU ruling, it is intended to enable the test bench to apply the Worldwide Harmonized Light Vehicles Test Cycle. Having a laboratorial test bench that can emulate vehicle dynamics under a specific drive cycle will allow small automotive manufacturers to confirm compliance with the mandatory drive cycles during different stages of their development. Nevertheless, other electric vehicles (EV) like boats or trains, can also be tested since the mathematical models of their dynamics are available.